ABNORMALITY AS DEPICTED IN PERFUME BY PATRICK SUSKIND (EUFONI: Journal of Language, Literary, and Cultural Studies, 2017)
This study is purposed to reval abnormality in best-seller novel, entitled Perfume.  The abnormality in this novel is reflected in two ways. They are social discomfort and violation. The theory of pshychoanalysis is applied in this study. The result of the study shows that social discomfort faced by the protagonist happens as the effect of his social status as lower class and his bad condition as an orphan. Meawhile, the violation occurs to the character because his tendency to hurt women for his obsession.Keywords: Abnormality, Social discomfort, Violation, Perfume